Francisella noatunensis subsp. orientalis outbreak in Nile tilapia juveniles cultivated in net cages in the Araguari river basin, Brazil (Research, Society and Development, 2021)
The aims at identifying and describing the occurrence ofanatomopathological  and  histopathological  changes  in  Nile  tilapia  juveniles, naturally infected with Francisella noatunensis subsp. orientalis (Fno). The Nile tilapias of this study were cultivated in net cages in the region of the Araguari River basin, Minas Gerais, Brazil, and due to a mortality rate ranging from 40 to 60%, 64 fish samples were collected and sent for examination in the laboratory. At  necropsy, granuloma-like  nodules  were  observed  in  the  spleen  59/64(92.2%), kidney 24/64 (37.5%), and liver 09/64 (14.1%). Fno was detected in 98% (49/50) of the samples by PCR. Upon analysis, astrong correlation was observed between external and internal lesions, since granulomatous lesions present in the spleen and kidney of the same animal simultaneously  were  also  accompanied  by skin  ulcers, suggesting  that  the cutaneous lesion is related to the presence of Fno in tilapia and can be used as an indication for early diagnosis. Thus, the high prevalence of Fno observed in this  research  study allows characterizing  an  outbreak  in  the  region.  It  is noteworthy that especially regarding the consumption of tilapia meat, although there are zoonotic species in the Francisella group, the zoonotic potential of Fno is not yet known and should be further studied.